A bottom-up implementation of Path-Relinking for Phylogenetic reconstruction applied to Maximum Parsimony - Vazquez-Ortiz, Karla E.; Richer, Jean-Michel; Lesaint, David; Rodriguez-Tello, Eduardo (2014 IEEE Symposium on Computational Intelligence in Multi-Criteria Decision-Making (MCDM), 2014)
In this article we describe a bottom-up implementation of Path-Relinking for Phylogenetic Trees in the context of the resolution of the Maximum Parsimony problem with Fitch optimality criterion. This bottom-up implementation is compared to two versions of an existing top-down implementation. We show that our implementation is more efficient, more interesting to compare trees and to give an estimation of the distance between two trees in terms of the number of transformations.